Research on the ecology of ticks and tick-borne pathogens—methodological principles and caveats - Estrada-Peña, Agustín; Gray, Jeremy S.; Kahl, Olaf; Lane, Robert S.; Nijhoff, Ard M. (Frontiers in Cellular and Infection Microbiology, 2013)
Interest in tick-transmitted pathogens has experienced an upsurge in the past few decades. Routine application of tools for the detection of fragments of foreign DNA in ticks, together with a high degree of interest in the quantification of disease risk for humans, has led to a marked increase in the number of reports on the eco-epidemiology of tick-borne diseases. However, procedural errors continue to accumulate in the scientific literature, resulting in misleading information. For example, unreliable identification of ticks and pathogens, erroneous interpretations of short-term field studies, and the hasty acceptance of some tick species as vectors have led to ambiguities regarding the vector role of these arthropods. In this review, we focus on the ecological features driving the life cycle of ticks and the resulting effects on the eco-epidemiology of tick-transmitted pathogens. We review the factors affecting field collections of ticks, and we describe the biologically and ecologically appropriate procedures for describing tick host-seeking activity and its correlation with environmental traits. We detail the climatic variables that have biological importance on ticks and explain how they should be properly measured and analyzed. We also provide evidence to critically reject the use of some environmental traits that are being increasingly reported as the drivers of the behavior of ticks. With the aim of standardization, we propose unambiguous definitions of the status of hosts and ticks regarding their ability to maintain and spread a given pathogen. We also describe laboratory procedures and standards for evaluating the vectorial capacity of a tick or the reservoir role of a host. This approach should provide a coherent framework for the reporting of research findings concerning ticks and tick-borne diseases.